2007
DOI: 10.1136/ard.2006.060905
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of leflunomide in primary Sjogren's syndrome: a phase II pilot study

Abstract: Background: For invalidating symptoms in primary Sjögren's syndrome (pSS), there is still a need for easy-toadminister, cost-effective and well-tolerated systemic treatment. Leflunomide (LEF) is structurally unrelated to other immunomodulatory drugs and might be efficacious in pSS, given its characteristic immunoregulatory modes of action. Objective: To investigate the safety and efficacy of LEF in pSS in a phase II open-label pilot study. Methods: 15 patients with pSS with early and active disease received LE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…A small open-label study with leflunomide 20 mg daily, including 15 patients with pSS with early and active disease, found no statistical significant difference in terms of perceived ocular dryness of objective improvement in the Schirmer test (44). No significant improvement of the ocular dryness was reported in studies with azathioprine (45) or oral cyclosporine (46), and the use of thalidomide was associated with prominent side-effects (47).…”
Section: Oral Treatmentsmentioning
confidence: 99%
“…A small open-label study with leflunomide 20 mg daily, including 15 patients with pSS with early and active disease, found no statistical significant difference in terms of perceived ocular dryness of objective improvement in the Schirmer test (44). No significant improvement of the ocular dryness was reported in studies with azathioprine (45) or oral cyclosporine (46), and the use of thalidomide was associated with prominent side-effects (47).…”
Section: Oral Treatmentsmentioning
confidence: 99%
“…[374][375][376] Subsequent results indicated that the treatment benefi ts and safety are durable for at least 2 to 5 years. 377,378 In addition to rheumatoid arthritis, clinical trials of lefl unomide as an antiinfl ammatory agent have been reported for Sjögren syndrome, 379 systemic lupus erythematosus, 380 and granulomatosis with polyangiitis. 381 Its use has also been described for sarcoidosis, 382 antisynthetase syndrome, 383 relapsing polychondritis, 384 adult-onset Still disease, 385 and arthritis associated with systemic sclerosis.…”
Section: Lefl Unomidementioning
confidence: 99%
“…LEF is teratogenic in rabbits and rats and is contraindicated in pregnancy. [ 7 ] performed a 24-week, open-label pilot study of LEF (20 mg weekly) on 15 women with pSS. All patients fulfi lled the European-American Consensus Criteria and had positive labial salivary gland biopsy (focus score ³ 1).…”
mentioning
confidence: 99%